1991
DOI: 10.2165/00003495-199141050-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release Nifedipine Formulations

Abstract: Nifedipine antagonises influx of calcium through cell membrane slow channels, and sustained release formulations of the calcium channel blocker have been shown to be effective in the treatment of mild to moderate hypertension and both stable and variant angina pectoris. Preliminary findings also indicate that these formulations are effective in the treatment of Raynaud's phenomenon and hypertension in pregnancy, and that they reduce the frequency of ischaemic episodes in some patients with silent myocardial is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 195 publications
1
10
0
Order By: Relevance
“…The GITS formulation of nifedipine has an oral bioavailability of 55-65% after a single dose and 75-85% at steady state. Plasma nifedipine concentrations begin to rise approximately 2 hours after oral administration and plateau approximately 6 hours later [4].…”
Section: Properties Of First-generation Calcium Channel Blockersmentioning
confidence: 99%
“…The GITS formulation of nifedipine has an oral bioavailability of 55-65% after a single dose and 75-85% at steady state. Plasma nifedipine concentrations begin to rise approximately 2 hours after oral administration and plateau approximately 6 hours later [4].…”
Section: Properties Of First-generation Calcium Channel Blockersmentioning
confidence: 99%
“…Microspheres have been widely accepted as a means to achieve an oral and parenteral controlled release drug delivery system [7] . Microspheres are better tolerated in the form of sustained release of nifedipine for their conventional counterparts and dosage [8] . Nifedipine is a prototype dihydropyridine calcium channel blocker with a rapid onset and a short duration of action [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The dihydropyridine ring of nifedipine is first oxidized to the pyridine ring, which is the main metabolite, and then further converted to other acidic metabolites 15 . Eventually, 70%–80% of nifedipine is eliminated in the urine as metabolites, with the remaining metabolites being eliminated in the feces 16,17 . Several drug‐drug interaction studies have been reported, ketoconazole, ginkgo biloba leaf extract, and Shengmai‐San increased the maximum plasma concentration (C max ) and area under the plasma concentration–time curve (AUC) of nifedipine due to their inhibitory effect on CYP 18–20 .…”
mentioning
confidence: 99%